Efektifitas Penggunaan Media Pembelajaran Menara Roda untuk Memberdayakan Peserta Didik Berkebutuhan Khusus - Prayitno Prayitno (Jurnal Didaktika Pendidikan Dasar, 2021)
Students with special needs at Tunjung 1 Public Elementary School have limited social interaction, verbal and emotional communication. Need to be trained in society to be given good opportunities, through special education services. Learning facilities that attract his attention need to be created, in order to help him socialize, play together without being disturbed, and can improve his academic achievement. For this reason, the writer created the "Wheel Tower". The goal is to empower students with special needs children with autism and improve academic achievement, especially in number patterns. These media are designed to be used jointly, and  individually. This media is in the form of stacked wheels that are arranged together, forming a flat shape (square, triangle, rectangle) from the large to the small one that resembles a tower. The shape of the tower shows a number pattern from small to large. From the learning process and results the use of "wheel towers" can empower students with special needs autistic children with regular children and can improve their academic achievement, especially in number patterns.